CORRELATION BETWEEN BODY SIZE AND MANY SIZES IN RAROWATU UTARA SUB-DISTRICT, BOMBANA REGENCY - Oktaviani, Astria; Aku, Achmad Selamet; Abadi, Musram (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2021)
This research was conducted in January 2019 until February 2019, located in North Rorowatu District, Bombana Regency. The purpose of this study was to determine body weight with body size (chest circumference, body length, shoulder height and hip height). Male and female goats in North Rarowatu District Bombana Regency. The material used in this study is adult male and female goats aged 12-24 years as many as 201 animals. The instrument used is a 50 kg scale with a capacity of 50 kg to measure life weight, a measuring tape to measure chest circumference, body length and a measuring stick to measure shoulder height, hip height. The results of this study indicate that the average body weight of male goats is 29.06 ± 5.85 kg and female goats are 23.75 ± 3.00 kg, chest circumference of male goats is 69.60 ± 5.83 cm and on goats females at 67.38 ± 7.92 cm, body length on male goats at 62.05 ± 6.46 cm and on female goats at 60.50 ± 8.46 cm shoulder height on male goats at 58.03 ± 4, 54 and in females 54.49 ± 7.65 cm, hip height in male goats was 59.44 ± 4.85 and in female goats 57.49 ± 7.75 cm. Based on the results of the study concluded there was a relationship between body measurements with body weight of goat nuts in North Rarowatu District. Chest circumference has the most close and very strong relationship to body weight as indicated by the correlation coefficient of 0.92 in males and 0.86 in females. Sequentially the results of the analysis of the correlation coefficient and determination are body weight - chest circumference 0.92 and 84.09% male, body weight - chest circumference 0.86-74.46% female, body weight - body length 0.68 and 46, 79% male, body weight - body length 0.70.48.89% female, body weight - shoulder height 0.60 and 36.36% male, body weight - shoulder height 0.64 and 40.98% female body weight - hip height 0.66 and 43.01% male, body weight - hip height 0.59 and 35.09% female.